Regulatory mechanisms behind the phenotypic plasticity associated with Setaria italica water deficit tolerance - Suguiyama, Vanessa Fuentes; Rodriguez, Jae Diana Paredes; Santos, Tatiane Cristina Nicomedio dos; Lira, Bruno Silvestre; de Haro, Luis Alejandro; Silva, João Paulo Naldi; Borba, Eduardo Leite; Purgatto, Eduardo; Silva, Emerson Alves da; Bellora Pereyra, Nicolás; Carrari, Fernando; Centeno, Danilo da Cruz; et al. (Springer, 2022)
Drought is one of the main environmental stresses that negatively impacts vegetative and reproductive yield. Water deficit responses are determined by the duration and intensity of the stress, which, together with plant genotype, will define the chances of plant survival. The metabolic adjustments in response to water deficit are complex and involve gene expression modulation regulated by DNA-binding proteins and epigenetic modifications. This last mechanism may also regulate the activity of transposable elements, which in turn impact the expression of nearby loci. Setaria italica plants submitted to five water deficit regimes were analyzed through a phenotypical approach, including growth, physiological, RNA-seq and sRNA-seq analyses. The results showed a progressive reduction in yield as a function of water deficit intensity associated with signaling pathway modulation and metabolic adjustments. We identified a group of loci that were consistently associated with drought responses, some of which were related to water deficit perception, signaling and regulation. Finally, an analysis of the transcriptome and sRNAome allowed us to identify genes putatively regulated by TE- and sRNA-related mechanisms and an intriguing positive correlation between transcript levels and sRNA accumulation in gene body regions. These findings shed light on the processes that allow S. italica to overcome drought and survive under water restrictive conditions.